PENGARUH PENERAPAN METODE PEMBELAJARAN COURSE REVIEW HOREY DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 BAYANG TAHUN PELAJARAN 2013/2014 - Rahmadani, Firanda; Husna, Husna; Aima, Zulfitri (Pendidikan Matematika, 2013)
This research is motivated by the low understanding of mathematical concepts grade 8 students in SMPN 1 Bayang. This study aims to determine the development of studentâs understanding of mathematical concept by applying instructional method of course review horey accompanied quiz. And to determine whether the studentâs understanding of mathematical concept trough course review horey accompanied quiz better than the studentâs understanding of mathematical concepts with conventional learning to grade 8 students of SMPN 1 Bayang.This type of research is experimental. The population is all students grade 8 at SMPN 1 Bayang in 2013/2014. Technique of taking sampling is taken randomly which is elected VIII.4 as experimental class and class VIII.2 as control class. The instruments used were the quizzes and final test indicators of understanding the concept. Form used was an essay test with a reliability of 0,75. Based on the analysis of data on studentâs understanding of mathematical concepts in the experimental class gained an average of the quizzes : 1st quis is 79, 2nd is 81,80, 3rd is 79,48 and 4th is 75,77. Hypothesis testing uses t-test of the parties, obtained 0,007 P-value less than Î±=0,05 significance level, the hypothesis is accept. It can be concluded that the studentâs understanding of the concept by applying the method mathematical learning of course review horey which is accompanied with quiz better than the studentâs understanding of mathematical concepts by applying the conventional learning at grade 8 SMPN 1 Bayang.